2015
DOI: 10.1007/s00439-015-1603-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between telomere length and chromosome 21 nondisjunction in the oocyte

Abstract: Chromosome 21 nondisjunction in oocytes is the most common cause of trisomy 21, the primary chromosomal abnormality responsible for Down syndrome (DS). This specific type of error is estimated to account for over 90% of live births with DS, with maternal age being the best known risk factor for chromosome 21 nondisjunction. The loss of telomere length and the concomitant shortening of chromosomes is considered a biological marker for aging. Thus, we tested the hypothesis that mothers who had a maternal nondisj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…In a previous study from our group (Albizua et al, ), we found a similar pattern of telomere length among women who had a child with trisomy 21 derived from a nondisjunction error in the oocyte compared with controls. In that study, we suggested that the reduced slope in the age‐related pattern reflected a biologically older stage; the telomeres were already shorter at the youngest ages studied and then declined less.…”
Section: Discussionsupporting
confidence: 78%
“…In a previous study from our group (Albizua et al, ), we found a similar pattern of telomere length among women who had a child with trisomy 21 derived from a nondisjunction error in the oocyte compared with controls. In that study, we suggested that the reduced slope in the age‐related pattern reflected a biologically older stage; the telomeres were already shorter at the youngest ages studied and then declined less.…”
Section: Discussionsupporting
confidence: 78%
“…One of the major limits for the study of the molecular mechanisms leading to chromosome 21 malsegregation is the unavailability of human egg cells from MDS, so that most of the studies aimed at linking folate metabolism to chromosome 21 malsegregation have been performed with surrogate cells and tissues, including peripheral lymphocytes [3][4][5][6][7]. In this regard, in vitro studies in human lymphocytes have shown that folate restriction induces chromosome 21 aneuploidy [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the studies performed so far in peripheral lymphocytes from MDS revealed that those cells are characterized by several markers of genome instability and premature ageing, including an increased frequency of micronuclei, short telomeres, and global changes in DNA methylation [3][4][5][6][7][8][9][10]. Those biomarkers could be indicators of altered pathways, such as impaired folate metabolism, accounting for an increased risk to give birth to a DS child in young age or to develop age-related neurodegenerative diseases later in life [3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With subsequent analyses of maternal molecular age, it has been proved that mothers of Down syndrome baby have shorter average telomere length than do the mothers of same chronological age and have euploid healthy baby [4,5]. The authors proposed that a group of women may suffer from advanced molecular and genetic aging and intuitively carry predisposition for NDJ.…”
Section: Introductionmentioning
confidence: 99%